Service System Innovation: An Ambidexterity Perspective - Wolf, Verena

Parameter- und Prozessoptimierung für den additiven Fertigungsprozess im Pulverbett am Beispiel der Legierung Ti6Al4V - Ahlers, Dominik
Die additive Fertigung mittels Laser Powderbed Fusion Verfahren (L-PBF) von Metallen wird zunehmend genutzt, um Funktionsbauteile endkonturnah zu fertigen. Die in der vor-liegenden Arbeit untersuchte Parameter- und Prozessoptimierung liefert einen Beitrag zur wirtschaftlichen Nutzung des L-PBF und zeigt, dass höhere Aufbauraten bei der ganzheit-lichen Betrachtung des Prozesses realisierbar sind. Die Parameter- und Prozessoptimierung erfordert eine Untersuchung des Einflusses der Fertigungs- und Nachbearbeitungsparameter auf das erzeugte Volumen sowie auf die Mikrostruktur und die resultierenden Materialeigenschaften. Das Ziel der vorliegenden Arbeit ist die Entwicklung einer optimierten Prozessführung mit abschließender Bewer-tung der Wirtschaftlichkeit. Mit dem entwickelten Gesamtprozess wird eine um den Faktor 1,6 höhere Aufbaurate erzielt. Des Weiteren wird die Methodik zur Erarbeitung des opti-mierten Prozessfensters beschrieben, sodass die Herangehensweise auf weitere Werk-stoffe angewendet werden kann. Die mechanischen Eigenschaften werden für den stati-schen und dynamischen Lastfall untersucht und mit der Mikrostruktur korreliert. Abschlie-ßend wird die Prozessoptimierung zur Fertigung eines Demonstrators eingesetzt und wirtschaftlich validiert. Die Ergebnisse zeigen, dass durch das hier angewendete Vorge-hen eine Prozesszeitreduktion von 22,5% und eine Kostenreduktion von 11% realisiert werden kann.
Keywords: Additive Manufacturing; SLM

Volunteer World GmbH – Schildkrötenretten als Business Case - Jakob, Eva Alexandra; Hansjürgen, Lea (Wettbewerbsfähigkeit von Start-ups, Erfolgreiche Düsseldorfer Unternehmen)

Electrochemical N2 Reduction to Ammonia Using Single Au/Fe Atoms Supported on Nitrogen-Doped Porous Carbon - Sahoo, Sudhir K.; Heske, Julian Joachim; Antonietti, Markus; Qin, Qing; Oschatz, Martin; Kühne, Thomas (ACS Applied Energy Materials)
The electrochemical nitrogen reduction reaction (NRR) to ammonia (NH3) is a promising alternative route for an NH3 synthesis at ambient conditions to the conventional high temperature and pressure Haber--Bosch process without the need for hydrogen gas. Single metal ions or atoms are attractive candidates for the catalytic activation of non-reactive nitrogen (N2), and for future targeted improvement of NRR catalysts, it is of utmost importance to get detailed insights into structure-performance relationships and mechanisms of N2 activation in such structures. Here, we report density functional theory studies on the NRR catalyzed by single Au and Fe atoms supported in graphitic C2N materials. Our results show that the metal atoms present in the structure of C2N are the reactive sites, which catalyze the aforesaid reaction by strong adsorption and activation of N2. We further demonstrate that a lower onset electrode potential is required for Fe--C2N than for Au--C2N. Thus, Fe--C2N is theoretically predicted to be a potentially better NRR catalyst at ambient conditions than Au--C2N owing to the larger adsorption energy of N2 molecules. Furthermore, we have experimentally shown that single sites of Au and Fe supported on nitrogen-doped porous carbon are indeed active NRR catalysts. However, in contrast to our theoretical results, the Au-based catalyst performed slightly better with a Faradaic efficiency (FE) of 10.1{%} than the Fe-based catalyst with an FE of 8.4{%} at −0.2 V vs. RHE. The DFT calculations suggest that this difference is due to the competitive hydrogen evolution reaction and higher desorption energy of ammonia.

Virtual screening of nitrogen-, phosphorous- and halide-containing materials as p-type transparent conductors - Wiebeler, Hendrik; Kormath Madam Raghupathy, Ramya; Mirhosseini, S. Hossein; Kühne, Thomas (Journal of Physics: Materials)
In this work, a high-throughput screening of binary and ternary pnictide- and halide-based compounds is performed to identify promising p-type transparent conductors. Our investigation profits from the emergence of open-access databases based on ab-initio results. The band gap, stability, hole effective mass, and p-type dopability are employed for the materials screening and the validity of these descriptors is discussed. Among the final candidates, BaSiN2 is the most promising compound.

NFDI4Culture - Consortium for research data on material and immaterial cultural heritage - Altenhöner, Reinhard; Blümel, Ina; Boehm, Franziska; Bove, Jens; Bicher, Katrin; Bracht, Christian; Brand, Ortrun; Dieckmann, Lisa; Effinger, Maria; Hagener, Malte; Hammes, Andrea; Heller, Lambert; et al. (Research Ideas and Outcomes)
Digital data on tangible and intangible cultural assets is an essential part of daily life, communication and experience. It has a lasting influence on the perception of cultural identity as well as on the interactions between research, the cultural economy and society. Throughout the last three decades, many cultural heritage institutions have contributed a wealth of digital representations of cultural assets (2D digital reproductions of paintings, sheet music, 3D digital models of sculptures, monuments, rooms, buildings), audio-visual data (music, film, stage performances), and procedural research data such as encoding and annotation formats. The long-term preservation and FAIR availability of research data from the cultural heritage domain is fundamentally important, not only for future academic success in the humanities but also for the cultural identity of individuals and society as a whole. Up to now, no coordinated effort for professional research data management on a national level exists in Germany. NFDI4Culture aims to fill this gap and create a user-centered, research-driven infrastructure that will cover a broad range of research domains from musicology, art history and architecture to performance, theatre, film, and media studies. The research landscape addressed by the consortium is characterized by strong institutional differentiation. Research units in the consortium's community of interest comprise university institutes, art colleges, academies, galleries, libraries, archives and museums. This diverse landscape is also characterized by an abundance of research objects, methodologies and a great potential for data-driven research. In a unique effort carried out by the applicant and co-applicants of this proposal and ten academic societies, this community is interconnected for the first time through a federated approach that is ideally suited to the needs of the participating researchers. To promote collaboration within the NFDI, to share knowledge and technology and to provide extensive support for its users have been the guiding principles of the consortium from the beginning and will be at the heart of all workflows and decision-making processes. Thanks to these principles, NFDI4Culture has gathered strong support ranging from individual researchers to high-level cultural heritage organizations such as the UNESCO, the International Council of Museums, the Open Knowledge Foundation and Wikimedia. On this basis, NFDI4Culture will take innovative measures that promote a cultural change towards a more reflective and sustainable handling of research data and at the same time boost qualification and professionalization in data-driven research in the domain of cultural heritage. This will create a long-lasting impact on science, cultural economy and society as a whole.

Der Darstellungsflüchtigkeit im Geometrieunterricht durch digitale Unterstützung entgegenwirken - Huhmann, Tobias; Eilterts, Katja; Schulte, Carsten; Winkelnkemper, Felix (Digitales Lernen in der Grundschule II: Aktuelle Trends in Forschung und Praxis)

Consulting via Research in IMPRESS - Ködding, Patrick; Reinhold, Jannik; Scholtysik, Michel; Dumitrescu, Roman (Journal of Systemics, Cybernetics and Informatics)

Pattern‐based development of digital platforms - Drewel, Marvin; Özcan, Leon; Koldewey, Christian; Gausemeier, Jürgen (Creativity and Innovation Management)

Social media in times of crisis: Learning from Hurricane Harvey for the coronavirus disease 2019 pandemic response - Mirbabaie, Milad; Bunker, Deborah; Stieglitz, Stefan; Marx, Julian; Ehnis, Christian (Journal of Information Technology)
In recent times societal crises such as the coronavirus disease 2019 outbreak have given rise to a tension between formal ‘command and control’ and informal social media activated self-organising information and communication systems that are utilised for crisis management decision-making. Social media distrust affects the dissemination of disaster information as it entails shifts in media perception and participation but also changes in the way individuals and organisations make sense of information in critical situations. So far, a little considered notion in this domain is the concept of sense-giving. Originating from organisational theory, it is used to explain the mechanisms behind intentional information provision that fosters collective meaning creation. In our study, we seek to understand the potential impact of sense-giving from Twitter crisis communication generated during the Hurricane Harvey disaster event. Social network and content analyses performed with a dataset of 9,414,463 tweets yielded insights into how sense-giving occurs during a large-scale disaster event. Theoretically, we specified (1) perpetual sense-giving, which relies primarily on topical authority and frequency; as well as (2) intermittent sense-giving, which occurs from high value of message content and leverage of popularity, that is, retweets. Our findings emphasise the importance of information-rich actors in communication networks and the leverage of their influence in crises such as coronavirus disease 2019 to reduce social media distrust and facilitate sense-making.

Behind the Review Curtain: Decomposition of Online Consumer Ratings in Peer-to-Peer Markets - Kaimann, Daniel (Sustainability)
Peer-to-peer markets are especially suitable for the analysis of online ratings as they represent two-sided markets that match buyers to sellers and thus lead to reduced scope for opportunistic behavior. We decompose the online ratings by focusing on the customer’s decision-making process in a leading peer-to-peer ridesharing platform. Using data from the leading peer-to-peer ridesharing platform BlaBlaCar, we analyze 17,584 users registered between 2004 and 2014 and their online ratings focusing on the decomposition of the explicit determinants reflecting the variance of online ratings. We find clear evidence to suggest that a driver’s attitude towards music, pets, smoking, and conversation has a significantly positive influence on his received online ratings. However, we also show that the interaction of female drivers and their attitude towards pets has a significantly negative effect on average ratings.

When are researchers willing to share their data? – Impacts of values and uncertainty on open data in higher education - Stieglitz, Stefan; Wilms, Konstantin; Mirbabaie, Milad; Hofeditz, Lennart; Brenger, Bela; López, Ania; Rehwald, Stephanie (PLOS ONE)

Virtually Extended Coworking Spaces – The Reinforcement of Social Proximity, Motivation and Knowledge Sharing Through ICT - Hofeditz, L.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 31st Australasian Conference on Information Systems)

Digital Detox – Mitigating Digital Overuse in Times of Remote Work and Social Isolation - Mirbabaie, Milad; Marx, J.; Braun, L.-M.; Stieglitz, S. (Proceedings of the 31st Australasian Conference on Information Systems)

‘Conspiracy Machines’ - The Role of Social Bots during the COVID-19 ‘Infodemic’ - Marx, J.; Brünker, F.; Mirbabaie, Milad; Hochstrate, E. (Proceedings of the 31st Australasian Conference on Information Systems)

A Systematic Review of Empirical Affordance Studies: Recommendations for Affordance Research in Information Systems - Fromm, J.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the Twenty-Eight European Conference on Information Systems)

The Usage of Twitter Data for Early Crisis Detection - Mirbabaie, Milad; Stieglitz, S.; Lambertz, L. (Proceedings of the 15th International Conference on Wirtschaftsinformatik)

‘The Tireless Selling-Machine’ – Commercial Deployment of Social Bots during Black Friday Season on Twitter - Brünker, F.; Marx, J.; Ross, B.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 15. Internationaler Kongress Für Wirtschaftsinformatik)

The Effects of Virtual Reality Affordances and Constraints on Negative Group Effects during Brainstorming Sessions - Fromm, J.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 15. Internationaler Kongress Für Wirtschaftsinformatik)

The Role of Social Media during Social Movements – Observations from the #metoo Debate on Twitter - Brünker, F.; Wischnewski, M.; Mirbabaie, Milad; Meinert, J. (Proceedings of the 51nd Hawaii International Conference on System Sciences)